Exploring and Implementing Nusantara Multiculturalism in History Learning in High School: Menggali dan Implementasi Multikulturalisme Nusantara dalam pembelajaran Sejarah di SMA - miskawi; Djono (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Indonesia, with its abundant cultural diversity, faces major challenges in implementing multiculturalism, especially among the younger generation. History learning based on the concept of Nusantara multiculturalism is in line with the values ​​of Pancasila. This study aims to explore the concept of Nusantara multiculturalism through historical studies and implement Nusantara multiculturalism in history learning at the high school level, with an emphasis on the application of Pancasila values. The research method used is a literature study, which collects information from various literature related to multiculturalism, Pancasila, and history education. The results of the study show that the concept of Nusantara multiculturalism has been laid as a strong foundation since the Majapahit Kingdom, emphasized by youth organizations and used as a guideline in national and state life based on Pancasila. The implementation of Nusantara multicultural education based on history learning can strengthen students' social awareness and nationalism, although there are challenges in its implementation, such as teacher readiness and curriculum limitations. Therefore, the development of a more inclusive curriculum and training for educators is very necessary.